Фізико-механічні властивості та структура полікристалічних матеріалів, отриманих з порошків cBN різної дисперсності - Беженар, М.П.; Лошак, М.Г.; Шульженко, О.О.; Александрова, Л.І.; Божко, С.А.; Білявина, Н.М.; Заіка, М.І. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2006)
The physical-mechanical properties РСBN, obtained by reactionary sintering with aluminium at high pressure and a heat from the сBN powders different dispersity were researched. Polycrystals from the submicronic powder, nanosize fractions containing, were retried aggregate size of an initial powder. Such РСBN had increased fracture toughness in comparison with a material of similar chemical and phase composition, but obtained of a micropowder.